Interdisciplinary approach of odontogenic infectious foci - a literature review - Julia Cabon; Karolina Ziaja; Anna Zawilska; Agata Trzcionka (Śląski Uniwersytet Medyczny w Katowicach, 2024)
Odontogenic foci are bacterial inflammatory changes, whose primary center is located in the area of the causal tooth. Various mechanisms result in the formation of secondary foci or systemic infections. Reliable diagnostics and elimination of the aforementioned foci are essential in the process of preparing patients qualified for ophthalmic surgery, organ transplants, dialysis, and anti-cancer therapy. Particular vigilance should also be exercised in the cases of patients with cardiovascular disease, especially those at high risk of infective endocarditis due to cyanotic congenital heart disease or an implanted valve prosthesis. The review paper presents the justification for conducting in-depth diagnostic and therapeutic procedures in the aforementioned groups of patients, citing methods for identifying the foci as well as methods for their elimination. The basic and overarching goal of the presented actions is to avoid complications in the form of severe infection and death.